2015
DOI: 10.1111/1744-7917.12182
|View full text |Cite
|
Sign up to set email alerts
|

Effect of photoperiod on slow and fast developing individuals in aphidophagous ladybirds, Menochilus sexmaculatus and Propylea dissecta (Coleoptera: Coccinellidae)

Abstract: The effects of environmental parameters on insect development have been studied extensively. But the reasons for 2 differential developmental rates within same cohort under varying environmental factors have not been explored. For the purpose, in this study the existence and stability of slow and fast development under 5 photoperiods (i.e., 8L: 16D, 10L : 14D, 12L : 12D, 14L : 10D and 16L : 8D; light and dark hours per day) and its effect on body mass and reproductive attributes in 2 aphidophagous ladybirds, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 96 publications
1
9
2
Order By: Relevance
“…), which differs from the ‘bimodal’ distributions reported by Mishra and Omkar () and Singh et al. (, ) for Menochilus sexmaculata and Propylea dissecta . Close examination of their results reveal that the sample sizes they used were a fifth to half the sample size used here, and more worrying is that the distributions recorded by Singh et al.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…), which differs from the ‘bimodal’ distributions reported by Mishra and Omkar () and Singh et al. (, ) for Menochilus sexmaculata and Propylea dissecta . Close examination of their results reveal that the sample sizes they used were a fifth to half the sample size used here, and more worrying is that the distributions recorded by Singh et al.…”
Section: Discussioncontrasting
confidence: 77%
“…The frequency distribution of the duration of development of larvae of A. bipunctata, all reared under similar conditions, is unimodal ( fig. 1), which differs from the 'bimodal' distributions reported by Mishra and Omkar (2012) and Singh et al (2014Singh et al ( , 2015 for Menochilus sexmaculata and Propylea dissecta. Close examination of their results reveal that the sample sizes they used were a fifth to half the sample size used here, and more worrying is that the distributions recorded by Singh et al (2014) for these two species differ from those previously recorded by these authors for the same species under the same conditions.…”
Section: Discussioncontrasting
confidence: 65%
“…Two predaceous ladybirds, M. sexmaculatus and P. dissecta, were selected for the study owing to their: (a) local abundance, (b) wide prey range, (c) fast development, (d) high reproduction and (e) previous studies on related aspects (Mishra & Omkar, 2012;Singh et al, 2014Singh et al, , 2016.…”
Section: Methodsmentioning
confidence: 99%
“…Bimodal (two peaks i.e., slow and fast) distribution has been reported not only in intraspecific body size (Gouws et al, 2011) but also in the developmental rates (Mishra & Omkar, 2012;Singh et al, 2014Singh et al, , 2016. The bimodal distribution and the proportion of slow:fast emergence has been found to shift in M. sexmaculatus and P. dissecta, with change in abiotic conditions like temperature and photoperiod (Singh et al, 2014(Singh et al, , 2016. The ratio of slow and fast developing individuals also differs with the biotic conditions, such as prey; poor prey species favoured the emergence of more slow developing individuals and vice versa (Singh et al, unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Ladybirds are potential biocontrol agents of a number of insect prey (Hodek et al, ), and intraspecific variation is common in developmental rates (Dixon, ; Hodek et al, ) and morphological traits (e.g., Mckinnon and Pierotti, ; Pech‐May et al, ). Recent studies in ladybirds have indicated the presence of slow and fast developers in a cohort (Mishra and Omkar, ; Singh et al, , ; Pandey et al, ) and potential environmen­tal as well as genetic control of this variation (Stern, ). Phenotypic plasticity for developmental rate in the ladybird, Hippodamia convergens (Guérin‐Méneville) has been successfully exploited to select for faster developing individuals (Rodriguez‐Saona and Miller, ).…”
mentioning
confidence: 99%